7-3x=2x-(5x-7)

Simple and best practice solution for 7-3x=2x-(5x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3x=2x-(5x-7) equation:



7-3x=2x-(5x-7)
We move all terms to the left:
7-3x-(2x-(5x-7))=0
We calculate terms in parentheses: -(2x-(5x-7)), so:
2x-(5x-7)
We get rid of parentheses
2x-5x+7
We add all the numbers together, and all the variables
-3x+7
Back to the equation:
-(-3x+7)
We get rid of parentheses
-3x+3x-7+7=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 2g+3g=40 | | 9x-8=8x+7 | | t/4+19=27 | | 8x−2=70 | | 7x-25-6=4 | | 30=6x=11x | | 54+37+x=180 | | 4x+5x=22 | | 3x-3+2=8 | | -13=-5f+48 | | 6.1+w/7=-5.1 | | .20f-14=1 | | 4^(x+1)=32 | | 54+37+x=90 | | 3u-37=4u-68 | | 4^x+1=32 | | 7+a÷3=5 | | -50x+30=330 | | 2/3(3x+12)=40 | | 4x+29=10 | | x*(1-x*x*x)=0.24 | | 3x+4x+1=8 | | 7x-6^2+9x-6^10=14 | | (x-3)(x+2)+2(x-3)=0 | | 4(x+3)+7=7 | | 2b=7b+20(V) | | -7.9=y/4-1.5 | | n=14-2n | | -30+10+2z=20 | | 16x-7+10x+5=180 | | m–23=63    | | -5=-6x+5x+2x+1 |

Equations solver categories